DFT mechanistic studies of boron–silicon exchange reactions between silyl-substituted arenes and boron bromides. Issue 9 (21st February 2023) - Qiu, Christopher S.; Qiu, Nicholas P.; Flinn, Christopher; Zhao, Yuming
Abstract : Our DFT calculations offer mechanistic insights into the exchange reactions between various silylarenes and boron bromides as well as potentially competing reaction pathways via electrophilic aromatic substitution. Abstract : C–B bond forming reactions are important methodologies in modern synthetic chemistry, since many borylated organic substrates, ranging from alkanes and alkenes to arenes and heteroarenes, are useful intermediates for the synthesis of natural products, pharmaceuticals, and organic π-conjugated materials. Among numerous borylation methods, C–Si/B–Br exchange reactions have attracted increasing attention in recent years. While experimental exploration has been continually carried out for more than two decades, mechanistic insights into this type of reaction have not yet been clearly established. To address this deficiency of knowledge, we performed density functional theory (DFT) calculations to map out the reaction pathways for a range of boron–silicon exchange reactions between boron tribromide (BBr3 ) and trimethylsilyl-substituted arenes (TMSAr). Our computational analyses have disclosed the energetic, structural, and electronic properties for key stationary points on the potential energy surfaces (PES) in both the gas and solution (CH2 Cl2 ) phases.